2018
DOI: 10.7441/joc.2018.02.04
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Recent Natural Disaster on the Japanese Financial Markets: Empirical Evidence

Abstract: The devastating Japan earthquake (magnitude 9.0) and tsunami (39-metre high) of 2011, also called the Great Tohoku or Sendai earthquake, was a record-breaker natural disaster causing enormous damage and a nuclear meltdown at Fukushima nuclear power plant. This paper attempts to analyse the long and short run effects of this record-breaking natural disaster on the Japanese equity, debt and FX markets as well as Gold as one of the most popular metals and investment options, using daily data. A variance bound tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…,Espinoza and Prasad (2010),Louzis et al (2012),Aktan et al (2018),Fakhry et al (2018) also found supportive results.Rossi, Schwaiger, and Winkler (2005) did research for the period from 1995 to 2002 on east and central European countries and stated that low efficiency can be associated with uncontrollable external factors.…”
mentioning
confidence: 52%
“…,Espinoza and Prasad (2010),Louzis et al (2012),Aktan et al (2018),Fakhry et al (2018) also found supportive results.Rossi, Schwaiger, and Winkler (2005) did research for the period from 1995 to 2002 on east and central European countries and stated that low efficiency can be associated with uncontrollable external factors.…”
mentioning
confidence: 52%
“…They also prove that the volatility of the stock markets is not affected by the earthquakes, except for Japan. Consistently, Fakhry et al (2018) find evidence that the influence of the Tohoku Earthquake on the financial markets is short lived. However, Valizadeh et al (2017) suggest that stock markets of Japan and its trading partners, such as China, United States, Germany, France, Italy and Spain, were not easily and immediately recovered after the earthquake.…”
Section: Japan Earthquake and Tsunamimentioning
confidence: 65%
“…Hence, the conditional volatility of stock market returns of Indonesia is positively influenced while they are negatively affected for the stock market of Vietnam. Despite the previous studies conducted by Ferreira and Karali (2015) and Fakhry et al (2018), which suggest that financial markets are resilient to earthquake shocks, the shocks that are constituted by 2011, Japan Earthquake are examined to be long-lived for all the considered stock market indices, except for the Indonesian stock market.…”
Section: Discussionmentioning
confidence: 93%
“…Research on the impact of natural disasters often focus on the short-term, leaving much of the long-term impact unexplored (Noy and DuPont, 2018;Fakhry et al, 2018;Chehabeddine, Tvaronavičienė, 2020). One could speculate that in the short-term, farms destroyed by disasters have no harvesting, factories damaged by disasters have little output and hence a negative impact on output is inevitable.…”
Section: Introductionmentioning
confidence: 99%